Penerapan Pembelajaran Berdifferensiasi Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika - Lestariani, Sri; Zahari, Cut Latifah; Salayan, Madyunus; Destiani, Rista (Universitas Asahan, 2024)
This study aims to apply differentiated learning to improve mathematical problem solving skills. This study uses a Classroom Action Research (CAR) design. This research consists of a cycle in cycle I which consists of four stages, namely (1) planning, which is the first stage in the research, the first stage which is carried out by compiling a learning plan and research instruments in accordance with the previous stages, (2) implementation, at the beginning of this the researcher carries out the learning process in accordance with the learning plan which has been previously planned, (3) implementation, this stage is carried out throughout the learning process to carry out all student activities in the implementation activities. test instrument to see students' problem solving abilities (4) reflection, this is done to find out the advantages and disadvantages of the learning process that has been carried out. This research was carried out at SMPN 2 Rawa Belonging with research subjects being students of class VII-1 in the academic year 2023/2024 with a total of 30 students consisting of 14 male students and 16 female students. Based on the results of this study, it is shown that the results of the test of students' mathematical problem solving ability increase for each cycle, so it can be concluded that the implementation of differentiated learning can increase students' mathematical problem solving ability. Keywords: Application, Differentiated Learning, Mathematical Problem Solving Ability